Cell trajectory modulation: rapid microfluidic biophysical profiling of CAR T cell functional phenotypes - Kerwin Kwek Zeming; Kai Yun Quek; Wei-Xiang Sin; Denise Bei Lin Teo; Ka-Wai Cheung; Chin Ren Goh; Faris Kairi; Elizabeth Lee; Francesca Lorraine Wei Inng Lim; Michaela Su-Fern Seng; Shui Yen Soh; Michael E. Birnbaum; et al. (Nature Communications)
Abstract Chimeric Antigen Receptor (CAR) T cell therapy is a pivotal treatment for hematological malignancies. However, CAR T cell products exhibit batch-to-batch variability in cell number, quality, and in vivo efficacy due to donor-to-donor heterogeneity, and pre/post-manufacturing processes, and the manufacturing of such products necessitates careful testing, both post-manufacturing and pre-infusion. Here, we introduce the Cell Trajectory Modulation (CTM) assay, a microfluidic, label-free approach for the rapid evaluation of the functional attributes of CAR T cells based on biophysical features (i.e., size, deformability). CTM assay correlates with phenotypic metrics, including CD4:CD8 ratio, memory subtypes, and cytotoxic activity. Validated across multiple donors and culture platforms, the CTM assay requires fewer than 10,000 cells and delivers results within 10 minutes. Compared to labeled flow cytometry processing, the CTM assay offers real-time data to guide adaptive manufacturing workflows. Thus, the CTM assay offers an improvement over existing phenotypic assessments, marking a step forward in advancing CAR T cell therapy manufacturing.